Treatment of early onset scoliosis - an early experience of growing rod insertion and lengthening - Mor Japar Khan, Ed Simor Khan; Ayu, Paul Ngalap; Jin, Hee Goh; Singh, Manmohan; Mohd Rashid, Mohd Zakhiri; Amir, Dzulkarnain; Mohamad, Fazir (2016)
Introduction Early onset scoliosis normally found in children from the age of birth till 10 years old with female preponderance. Any lateral spinal curvature of 10 degrees or more by reference to Cobb's angle measurement is diagnosed as scoliosis. The deformities is three dimensional thus affecting spinal growth in multiple planes. Scoliosis has been classified based on it's underlying causes such as congenital, idiopathic and also secondary causes as neuromuscular scoliosis or syndromic scoliosis.